ANALISIS NILAI NASIONALISME DALAM NOVEL MATA DAN RAHASIA PULAU GAPI KARYA OKKY MADASARI - Sriwidayati, Eka; Hidayat, Muhamad Taufik (STIT AL MULTAZAM, 2023)
Nationalism is an attitude of love and pride for the motherland. The value of nationalism comes from the spirit of nationalism by the people to defend the country. Not only by trying to protect the land but also by being proud of the cultures. This study aimed to analyze and describe the content of nationalism values in the novel